Aerobic granular sludge for complex heavy metal-containing wastewater treatment: characterization, performance, and mechanisms analysis - Liu, Chong; Shen, Yao; Li, Yuguang; Huang, Fengguang; Wang, Shuo; Li, Ji (Frontiers in Microbiology, 2024)
Complex heavy metal (HM)-containing wastewater discharges pose substantial risks to global water ecosystems and human health. Aerobic granular sludge (AGS) has attracted increased attention as an efficient and low-cost adsorbent in HM-containing wastewater treatment. Therefore, this study systematically evaluates the effect of Cu(II), Ni(II), and Cr(III) addition on the characteristics, performance and mechanism of AGS in complex HM-containing wastewater treatment process by means of fourier transform infrared spectroscopy, inductively coupled plasma spectrocopcy, confocal laser scanning microscopy, extracellular polymeric substances (EPS) fractions detection and scanning electron microscope-energy dispersive X-ray. The results showed that AGS efficiently eliminated Cu(II), Ni(II), and Cr(III) by the orchestrated mechanisms of ion exchange, three-layer EPS adsorption [soluble microbial products EPS (SMP-EPS), loosely bound EPS (LB-EPS), tightly bound EPS (TB-EPS)], and inner-sphere adsorption; notably, almost 100% of Ni(II) was removed. Three-layer EPS adsorption was the dominant mechanism through which the HM were removed, followed by ion exchange and inner-sphere adsorption. SMP-EPS and TB-EPS were identified as the key EPS fractions for adsorbing Cr(III) and Cu(II), respectively, while Ni(II) was adsorbed evenly on SMP-EPS, TB-EPS, and LB-EPS. Moreover, the rates at which the complex HM penetrated into the granule interior and their affinity for EPS followed the order Cu(II) > Ni(II) > Cr(III). Ultimately, addition of complex HM stimulated microorganisms to excrete massive phosphodiesterases (PDEs), leading to a pronounced decrease in cyclic diguanylate (c-di-GMP) levels, which subsequently suppressed EPS secretion due to the direct linkage between c-di-GMP and EPS. This study unveils the adaptability and removal mechanism of AGS in the treatment of complex HM-containing wastewater, which is expected to provide novel insights for addressing the challenges posed by intricate real wastewater scenarios.